Potential Impact of Climate Change on Groundwater Level Declination in Bangladesh: A Mathematical Modeling Computation (Informatica, 2023)
Groundwater is one of the most important natural resources for the human being due to its ecological diversity. It has become a vastly vital and dependable source of water in all climatic regions together with each urban and rural areas of developed and developing countries like Bangladesh. Groundwater level declines for many reasons, some of which occurs due to natural phenomena and others are caused by human’s activities and it has been declining since the introduction of deep tube wells and shallow tube wells after 1970s. Excessive demand of water, evaporation, pollution, deforestation, poor storage, low rainfall, urbanization, frequent pumping of water are the important causes of groundwater level declination in Bangladesh as well as all over the world. Taking these potential effects of climatic change into account, we formulate a mathematical model of groundwater level declination with the help of a system of nonlinear ordinary differential equations (ODEs). The model has been analyzed by finding the existence of equilibrium points and also the conditions of stability and instability near the equilibrium points have been derived by using the stability theory of non-linear differential equations with Lyapunov function and phase portrait analysis. Finally, the numerical simulations have been performed to illustrate the effect of pollution, deforestation, frequent pumping of water and evaporation on the groundwater level in support of analytical findings. Our study shows that, groundwater level decreases significantly due to over pumping, pollution, deforestation and global warming.